Keputusan Berkunjung Wisata Ke Dunia Fantasi (DUFAN) Yang Dipengaruhi Oleh Fasilitas Tempat Wisata Dengan Loyalitas Sebagai Variabel Mediasi - Nurul Aisyah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The purpose of writing this research is to find out the Decision to Visit a Tour to Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol which is influenced by tourist facilities with visitor loyalty as a mediating variable. This type of research is explanatory research which explains the causal relationship between the variables through hypothesis testing. This study used a sample of 100 respondents, these respondents were individuals who had visited Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol 2 times, were aged more than or equal to 17 years, and were decision makers. By using non-probability sampling technique. Hypothesis testing is done by T test and Sobel test. Data analysis uses Partial Least Square (PLS) and is assisted by SmartPLS 3.0 software to facilitate research. From the results of this test it can be concluded that the variable tourist facilities has a positive and significant effect on the decision to visit a tour to Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol. Variable Tourist attractions facilities have a positive and significant effect on Loyalty visiting a tour to Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol. Loyalty variable visits have a positive and significant effect on the decision to visit a tour to Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol. Variable tourist facilities positive and significant to the decision to visit a tour to Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol with visitor loyalty as a mediating variable